Power Output of Two Semiconductor Lasers: An Observational Study - Vicky Wenqing Xue; Iris Xiaoxue Yin; John Yun Niu; Kenneth Luk; Edward Chin Man Lo; Chun Hung Chu (Photonics, 2022)
The objective of this study was to evaluate the power output of two dental devices. The study examined two semiconductor lasers, namely, SIROLaser Blue (445 nm, 970 nm) and Picasso (810 nm). The power output performance was studied at the maximum output power of the devices. The study compared the preset power output measured by a power meter in a continuous-wave mode and in pulsed mode at 50% duty cycles. Ten 60 s measurements were performed for each setting. The largest difference between the stipulated and the actual output power at continuous-wave (D-cw) and pulsed (D-p) modes was calculated. Moreover, the percentage variations in the mean output power at continuous-wave (%D-cw) and pulsed (%D-p) modes were calculated. The D-cw values for 445 nm, 970 nm, and 810 nm lasers were 0.7 W, 0.5 W, and −0.3 W, respectively, and %D-cw values were 21%, 23%, and −8%, respectively. The D-p values for 445 nm, 970 nm, and 810 nm lasers were 1.1 W, 0.5 W, and −0.1 W, respectively, whereas the %D-p values were 37%, 26%, and −3%, respectively. This study found that the actual power is not necessarily lower but can be higher than the displayed power output. Clinicians are recommended to calibrate the laser output by using a power meter before use.